Climate-Induced Migration: A Legal Examination of Victims’ Rights in International Law - Arshad Nawaz Khan; Dr. Bahadar Ali; Bilal Hafeez (Journal of Peace, Development and Communication, 2023)
Environmental disturbance causes dramatic climate-induced migration. Basic survival requires relocation. This study uses transitional legal studies as theoretical framework to examine the complicated interaction between climate-induced migration and international law. Beyond theoretical frameworks, it investigates practical ramifications using legal paradigms, real-world case studies, and concrete solutions. This extensive study aims to advance climate justice and protect environmental displacement victims’ rights. Transitional legal studies explain how legal norms change and interact. Based on transitional legal studies, the study examines essential rights applicable to climate-induced migration, such as no refoulement, non-discrimination, and life. The report emphasises the necessity for a flexible legal framework to manage climate change’s changing issues. A detailed analysis of the legal framework reveals successes and areas for improvement, enabling tailored recommendations. The research recommends international legal recognition of climate refugees. An international accord on climate-induced migration suggests a more comprehensive legal revision. Global funding that address adaptation and migration costs assures global accountability. The analysis uses real-world case studies to examine the practical challenges of adapting the present legal system to climate-induced migration.Flexible and sensitive legal solutions are needed after the Carteret Islands and Bangladesh’s climate refugees’ horrific experiences. The paper analyses the international legal system theoretically and legally and makes practical recommendations to enhance it. These include improving indigenous knowledge integration, capacity building, and interagency coordination and collaboration. The broad data sharing and research programme and regular legislative framework review and adjustment reflect the commitment to evidence-based policy making. This paper concludes by linking theoretical and practical concepts to contribute to the international law discussion on climate-induced migration.These initiatives aim to provide a solid legal framework that protects people’s rights and dignity in a rapidly changing world due to environmental displacement.